MEDICAL STUDENTS’ REFLECTION ON CHEATING, ALTRUISM AND PLAGIARISM: A QUALITATIVE STUDY - Wiwik Kusumawati; Titi Savitri Prihatiningsih; Gandes Retno Rahayu; Soenarto Sastrowijoto (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2018)
Background: Derogation of professional behavior (PB) increased in education, even in medical education revealed cheating during in educational process as best predictor when the students at work placed in the future. The aim of this study is to know the students’ perspective on cheating, altruism and plagiarism.Method: This study was conducted using a qualitative approach. Sampling technique was purposeful sampling with criterion reference. Fifty-two year-one students of medical school of faculty of medicine and health sciences (FMHS) divided into 5 groups, each group consists of 10 to 11 students. The students received teaching learning of PB (three times tutorial with trigger film, reflection and expert panel). Qualitative data from students’ reflection analized using constant comparative method. Results: The results of this study indicated the presence of 6 final themes (i.e., learning value, learning approach, student preparedness, examination strategy, learning spiritual, study plan. Students who had the ability to understand various learning events would have a good study plan, and then could choose appropriate examination strategy to reach success and could avoid blamable event such as cheating. The students who had good learning spiritual and learning value to dilemmatic event, they would be motivated and their heart would be touched, so in their future plan they would try to be altruistic and professional doctor in all situation. There would be influence on positive study plan, make more effort and pried to God, also respect others work, so plagiarism could be avoided.Conclusion: There were 6 final themes of students’ reflection on cheating, altruism and plagiarism after they exposure by teaching learning of PB. They were learning value, learning approach, student preparedness, examination strategy, learning spiritual and study plan.